INTEGRATING ARTIFICIAL INTELLIGENCE TOOLS INTO ENGLISH LANGUAGE TEACHING: ENHANCING STUDENTS’ COMMUNICATIVE COMPETENCE IN HIGHER EDUCATION - Khorunova Sabokhat (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: Artificial Intelligence (AI) has become one of the most influential innovations in modern education, creating new opportunities for improving the quality of English language teaching and learning. AI-powered educational technologies enable teachers to design personalized learning experiences, provide instant feedback, and encourage learner autonomy. This paper explores the role of artificial intelligence in developing students’ communicative competence in higher education. It discusses the pedagogical benefits of integrating AI tools into English language classrooms, particularly in English for Specific Purposes (ESP) courses. The study also highlights the challenges related to academic integrity, ethical AI use, and teachers’ digital competencies. The findings suggest that AI should be viewed as a supportive educational assistant rather than a replacement for teachers. Appropriate implementation of AI technologies can significantly improve students’ language proficiency, critical thinking, creativity, and digital literacy while enhancing teaching effectiveness.